Dynamic colour change in zebrafish (Danio rerio) across multiple contexts - Ella J. Ackroyd; Robert J. P. Heathcote; Christos C. Ioannou (Royal Society Open Science)
Many animals are capable of rapid dynamic colour change, which is particularly well represented in fishes. The proximate mechanisms of dynamic colour change in fishes are well understood; however, less attention has been given to understanding its ecological relevance. In this study, we investigate dynamic colour change in zebrafish (Danio rerio) across multiple contexts, using a protocol to image the colouration of live fish without anaesthesia under standardized conditions. We show that zebrafish respond to different visual environments by darkening their overall colouration in a dark environment and lightening in a light environment. This is consistent with crypsis through background matching as a function of dynamic colour change. Additionally, we find that zebrafish use dynamic colour change to increase the internal contrast of their striped patterning in the presence of conspecifics. We speculate that this may function in social signalling and/or dazzle colouration. We find no effect of a predator stimulus on dynamic colour change. Finally, we discuss the potential for zebrafish to use multiple colouration strategies simultaneously as distance-dependent effects, considering the typical viewing distances of zebrafish and their predators.